“I travel myself”: nomadic motives originating from the Balkans (Colloquia Comparativa Litterarum, 2025)
The article examines the special role of the journey - spiritual and physical, in three novels by immigrant authors from the Balkans: Paris-Athens by Vassilis Alexakis, Hotel Europe by Dumitru Tsepeneag and Murder in Byzantium by Julia Kristeva. Represented is the idea that, by leaving his motherland, the immigrant could never attach himself the same way to any place and be fully accepted in the new community. Thus, his constant movement appears as a peculiar reaction to this specific ‘uprooting’ and becomes a way of life and thinking – i.e. a modern ‘nomadism’.
Keywords: Comparative Balkan literature; migration; identity; otherness; nomadism; Vassilis Alexakis; Dumitru Tsepeneag; Julia Kristeva